Religious Counseling Strategy in Providing Consultation Services on Domestic Violence Through BP4 Function - Manab, Abdul; Tarakal, Sri Utami (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
This research highlights the primary issue of how religious counselors use the BP-4 function to provide consultation services on domestic violence in the KUA, Biromaru District, Sigi Regency. This research employs a qualitative approach and is situated in the KUA, Biromaru District, Sigi Regency. The approach used is a descriptive one. The data sources used for this research are primary data, and secondary data are book literature, journals, and written documents. Data collection methods include observation, interviews, and documentation. Data processing and analysis techniques include data reduction, data presentation, and conclusion drawing. The research findings indicate that religious counselors are making significant efforts to provide consultation services related to domestic violence, including family guidance, mediation, and family advice through taklim assemblies. The inhibiting factors experienced by religious counselors in providing consultation services regarding domestic violence are difficulty in bringing together both parties who have domestic violence problems and parental interference in the problem.